Ergebnisse der Albanien-Expedition 1961 des Deutschen Entomologischen Institutes. 21. Beitrag: Thysanoptera. - Pelikán, Jaroslav (Contributions to Entomology = Beiträge zur Entomologie, 1964)
The above paper contains the determination of the Thysanoptera collected by the expedi-tion of the Deutsches Entomologisches Institut to Albania, as well as a complete list species known from this country up to the present time. The material collected, 163 specimens, represents 21 species, 9 of which are new to the fauna of Albania; Haplothrips dudichi Priesner is new to the Balkan countries. Now there are known 67 species of this order from Albania, including 2 species (Hoplothrips ripicola Priesner, and Rhynchothrips glaber Priesner) which are known up to now from Albania only.